Is menstrual delay a serious problem for elite rhythmic gymnasts? - Di Cagno, A.; Marchetti, M.; Battaglia, C.; Giombini, A.; Calcagno, G.; Fiorilli, G.; Piazza, M.; Pigozzi, F.; Borrione, P. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aim of this study was to identify the influence of training workloads and dietary habits on the menstrual status of elite rhythmic gymnasts. In many sports disciplines, it has long been assumed that menstrual disorders among elite female athletes are related to intense physical effort and insufficient energy intake. Potential consequences of this condition include reduced fertility and decreased bone density.